Systematic assessment of irregular building-soil interaction using efficient modal analysis. - Wu, Wen-Hwa (Earthquake engineering & structural dynamics.)
In this paper an efficient methodology applying modal analysis is developed to assess systematically the combined soil structure interaction and torsional coupling effects on asymmetric buildings. This method is implemented in the frequency domain to accurately incorporate the frequency dependent foundation impedance functions. For extensively extracting the soil structure interaction effects, a diagonal transfer matrix in the modal space is derived. A comprehensive investigation of asymmetric building soil interaction can then be conveniently conducted by examining various types of response quantities. Results of parametric study show that the increasing height to base ratio of a structure generally amplifies its translational and torsional responses. Moreover, both the translational and torsional responses are reduced for the case where the two resonant frequencies are well separated and this reduction is enhanced with the decreasing values of the relative soil stiffness and the height to base ratio. The most noteworthy phenomenon may be the fact that the SSI effects can enlarge the translational response if the structure is slender and the two resonant frequencies are very close.